Mathematic Perception In Whatsapp Group Interaction Teacher Participant PPG UHAMKA Year 2020 - Wahidin Wahidin (Universitas Negeri Makassar, 2021)
This descriptive qualitative research aims to see the mathematical perceptions of the teachers participating in the 2020 PPG Daljab UHAMKA after being given the question